2006
DOI: 10.1534/genetics.106.056895
|View full text |Cite
|
Sign up to set email alerts
|

A Defect in Protein Farnesylation Suppresses a Loss of Schizosaccharomyces pombe tsc2+, a Homolog of the Human Gene Predisposing to Tuberous Sclerosis Complex

Abstract: Mutations in the human Tsc1 and Tsc2 genes predispose to tuberous sclerosis complex (TSC), a disorder characterized by the wide spread of benign tumors. Tsc1 and Tsc2 proteins form a complex and serve as a GTPase-activating protein (GAP) for Rheb, a GTPase regulating a downstream kinase, mTOR. The genome of Schizosaccharomyces pombe contains tsc1 1 and tsc2 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 52 publications
(40 reference statements)
4
39
0
Order By: Relevance
“…These results indicate that the growth defect of Dtsc2 cells is mainly due to leucine auxotrophy. Consistently, it is demonstrated that leu1-32 Dtsc2 failed to grow on PM media containing 40-200 mg/ml leucine Nakase et al 2006). As reported previously (van Slegtenhorst et al 2004;Nakase et al 2006) and as shown in Figure 1C, the prototrophic Dtsc2 cells displayed canavanine resistance.…”
Section: Miscellaneous Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…These results indicate that the growth defect of Dtsc2 cells is mainly due to leucine auxotrophy. Consistently, it is demonstrated that leu1-32 Dtsc2 failed to grow on PM media containing 40-200 mg/ml leucine Nakase et al 2006). As reported previously (van Slegtenhorst et al 2004;Nakase et al 2006) and as shown in Figure 1C, the prototrophic Dtsc2 cells displayed canavanine resistance.…”
Section: Miscellaneous Methodssupporting
confidence: 88%
“…In fission yeast, several lines of evidence have demonstrated that Tsc2 functions as GAP for the small GTPase Rhb1 (van Slegtenhorst et al 2004(van Slegtenhorst et al , 2005Urano et al 2005;Nakase et al 2006), and Rhb1 positively regulates Tor2 activity (Urano et al 2005;Uritani et al 2006). Based on these reports we reasoned that isolation of the mutant strains that phenocopy Dtsc2 cells will identify novel negative regulators of Tor2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike budding yeast, fission yeast encodes apparent orthologues of mammalian TSC1 and TSC2. Furthermore, genetic studies in fission yeast are consistent with TSC and Rheb orthologues functioning, respectively, to antagonize and stimulate a TORC1-like activity (Mach et al, 2000;Yang et al, 2001;Tabancay et al, 2003;van Slegtenhorst et al, 2004;Urano et al, 2005;Nakase et al, 2006). There is considerable debate regarding the mechanisms by which Rheb regulates mTORC1 (Wullschleger et al (2006) and described elsewhere in this issue); perhaps studies in a genetically tractable organism like S. pombe will help settle these controversies.…”
Section: Future Directionsmentioning
confidence: 95%
“…Like mammalian cells, Rhb1p is down-regulated by the Tsc1p/Tsc2p complex (21,22). Mutations in the tsc genes result in a delayed response to nitrogen starvation as well as defects in amino acid uptake (21)(22)(23)(24)(25). The fission yeast genome encodes two TOR proteins, Tor1p and Tor2p (26,27).…”
mentioning
confidence: 99%